[PP.28.13] DIFFERENCES IN THE MONITORING AND DYSFUNCTION OF THE AUTONOMIC NERVOUS SYSTEM IN PATIENTS WITH TYPE 1 AND TYPE 2 DIABETES. (September 2016) - STOJANOVIC, M.; Nisic, T.; Lalic, T.; Stojkovic, M.; Beleslin, B.; Ciric, J.; Savic, S.; Zarkovic, M.; Barac, M.; Vujovic, S.; Stojanov, V.
Abstract : Objective: Dysfunction of the autonomic nervous system can be diagnosed by spectral analysis of variability of cardiac frequencies of consecutive RR interval using TASK FORCE monitor. Design and method: Methodology and results: Study was done using TASK FORCE monitor and software analysis of HRV Fourier transform algorithm. Testing at rest (20 min) and passive orthostasis (tilt table 90° for 6 minutes and parameters from ambulatory blood pressure monitoring (ABPM) device Meditech ABPM 05. Diagnostic procedures were done in 110 patients, of which 48 treated for type 1 diabetes, average age 37 years, of which 28 men and 20 women. The second group contained 62 patients with type 2 diabetes, average age 62 years of which 35 men and 27 women. Results: In groups with type 1 diabetes LF HF at rest X ∼ 1.745 ± 0.91 SD; LF HF orthostasis X ∼ 3.08 ± 2.65 SD; LF-DBP at rest 44.79 SD ± 16:52; LF DBP orthostasis X ∼ 51.91SD ± 11:41, HF RRI at rest 36.01 SD ± 14.65, HF RRI orthostasis X ∼ 25.98 SD ± 8.2; BRS at rest 10.1,  ± SD 6.18. In the group with type 2 diabetes LF HF at rest X ∼ 4.01 The SD ± 7.02, LF / HF orthostasis X 4.7 ± 8.9, LF DBP at rest X ∼ 37.17 ± 14.85, LF DBP orthostasis X ∼ 37.32 ± 10.89, HF RRI at rest 43.51, SD ± 17:48, HF RRI orthostasis X 43.51 ± 23:30, BRS at rest SD 9.78 ± 6.50. Correlation between the groups showed highly significant difference for LF DBP in orthostasis (p < 0.00067). Conclusions: Conclusion: Significantly lower values of LF DBP were registered in the group with type 2 diabetes, which represents the FAILURE of SYMPHATETIC in orthostasis. Orthostasis has been shown in ABPM analysis as well. It is common that patients with diabetes have a dominant parasympathetic dysfunction.